Influential Factors of Sustainable Entrepreneurial Intention Among Gen Y and Z Women in Indonesia - Palumian, Yonathan; Millenia, Gabriella; Sahetapy, Wilma Laura; Rahayuningrat, Prahita Sri (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
The objective of this study is to enhance our understanding of the factors that influence women's long-term intentions to become entrepreneurs. Specifically, it focuses on examining how perceived capability and social perception impact the intention to become a sustainable entrepreneur, with perceived opportunity acting as a mediating factor. This research adopts an explanatory approach and employs a quantitative methodology, involving a sample of 204 respondents who participated in an online questionnaire-based survey. By utilizing SmartPLS 4.0 software, this study demonstrates that perceived capability, social perception, and perceived opportunity significantly influence the intention of Indonesian women from Gen Y and Z to become sustainable entrepreneurs. Furthermore, perceived opportunity plays a notable mediating role among the other three variables.